Comparison of Doppler ultrasound and transient elastography in the diagnosis of significant fibrosis in patients with nonalcoholic steatohepatitis - ÇELİKEL, ÇİĞDEM; TÜNEY, DAVUT; BUĞDAYCI, ONUR; ERGELEN, RABİA; YILMAZ, YUSUF (SPRINGER, 2016)
Background: Liver fibrosis is an important prognostic determinant in patients with nonalcoholic steatohepatitis (NASH). Hepatic artery resistivity index (HARI) is a doppler ultrasonography (US) parameter that is used to follow up microcirculatory resistance in fatty liver. We aimed to asses whether it is possible to demonstrate significant fibrosis by means of doppler US in comparison with transient elastography (TE) and liver biopsy in NASH patients. Patients and methods: A total of 63 (mean age 47.1 +/- 8.4 years, 39 male, 24 female) biopsy-proven NASH patients were enrolled in this prospective study. The study population was classified into two groups: significant and no-significant fibrosis patients. Doppler US and TE were performed in two groups. Results: HARI and TE values were significantly higher in significant fibrosis group (0.81 +/- 0.05 vs. 0.63 +/- 0.14, p < 0.0005; 15.9 +/- 4.8 vs. 6.2 +/- 2.6 kilopascals, p < 0.0005; respectively). Based on the ROC curve, the optimal cut-off value of HARI for a significant fibrosis was >0.75, which yielded a sensitivity of 78% and a specificity of 75%, with the area under the curve at 0.90. The optimal cut-off value of TE for a significant fibrosis was >9.8 kilopascals, which yielded a sensitivity of 90% and a specificity of 91%, with the area under the curve at 0.95. HARI values were moderately correlated with TE values (r = 0.53, p < 0.001). Conclusion: Doppler US has moderate % sensitivity and % specificity, which is lower compared with TE for the diagnosis significant fibrosis. However, it may be used as an alternative method for the assessment of fibrosis in patients with NASH who are not good candidates for TE evaluation.
Keywords: Fatty liver; Doppler; Fibroscan; Non-alcoholic; FATTY LIVER-DISEASE; CHRONIC HEPATITIS-B; STIFFNESS MEASUREMENT; CLINICAL-APPLICATION; VIRAL-HEPATITIS; BIOPSY; FIBROTEST; CIRRHOSIS; ARTERY; INDEX